Lucky in love - West, Kasie (New York, NY : Point, 2017)
Maddie is a hard working high school senior, waiting to hear from the colleges she applied to, when on a whim she buys a lottery ticket and wins; suddenly she is the center of everybody's attention, including her struggling family, and not necessarily in a good way--only Seth Nguyen, her charming coworker at the local zoo, seems oblivious to her luck, and Maddie is not sure whether telling him will change their developing relationship.
Accelerated Reader AR
Keywords: Lottery winners -- Juvenile fiction; Fortune -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Families -- Juvenile fiction; Siblings -- Juvenile fiction; Friendship -- Juvenile fiction; Lotteries -- Fiction; Luck -- Fiction; Interpersonal relations -- Fiction; Family life -- Fiction; Brothers and sisters -- Fiction; Friendship -- Fiction; JUVENILE FICTION -- Family; JUVENILE FICTION -- Love & Romance; JUVENILE FICTION -- Social Themes -- Friendship; Brothers and sisters; Families; Fortune; Friendship; Interpersonal relations; Lottery winners; Family life -- Fiction; Luck -- Fiction; Friendship -- Fiction; Brothers and sisters -- Fiction; Lotteries -- Fiction; Interpersonal relations -- Fiction; Romance fiction; Fiction; Juvenile works; Romance fiction; Fiction; Juvenile works; Love stories; Romance fiction